Planeamento, operacionalização e intervenção numa equipa de Futebol do Campeonato Nacional Juniores C, na época 2017/2018: Relatório de Estágio Profissionalizante na equipa Sub-14 do Futebol Clube do Porto - Futebol-SAD - Diogo Bernardo Medeiros (2018)
In the last years, the quality of Portuguese football has reached levels of excellence through the achievement of several titles recognized by the world of football and the presence of several Portuguese coaches in the largest football competitions in the world. The multidimensional vision in soccer misinterpreted mechanized and shaped a football match that is only focus on the goal, to score and not to suffer. The bad articulation of all these areas, which supports the training and the player development, have sometimes resulted in such mechanization that turns the matches predictable, without creativity, essence and finally without emotion. This internship report is the conclusion of this Master's Degree in High Performance Training at the Faculty of Sport of the University of Porto, and was held in the Futebol Clube do Porto, in the U-14 team, during the season 2017/2018.As I did my internship in a club with this dimension, my expectative are high regarding the impact that will have on my profession skills as a coach. Concluded the internship and the accomplishment of this document, I understood that my inicial expectative were reached, and as will be confirmed in this work in same way they were overcame.The cult of a winning and demanding mentality was a decisive factor for the team's success this season. Learning and understanding the game principles was the most important thing to get our form of play, supported also by a methodology that could make the intended play emerge. These bases were the ones that gave identity and characteristics to the team itself. From the practical experience gained throughout year in the club, I can conclude that the club has a concern to develop talented players. There are some strategies, such as: 1) Changing the game model, with the aim of empowering, developing players more comprehensive and punishing;2) Creation of a training / play model without compulsory paths, through the creation of contexts where autonomy, intelligence and unpredictability are stimulated; 3) Definition of the teams respecting the growth rate of each one; 4) Hold regular meetings with parents.